Architektur der Bildungsoffensive. Die NRW-Gesamthochschulen - Seng, Eva- Maria (Junge Hochschulen“ – wissenschafts- und hochschulpolitische Herausforderungen seit der 2. Hälfte des 20. Jahrhunderts)

Forschungsstand zu Bewegung, Spiel und Sport im schulischen Ganztag in Deutschland: ein Scoping Review - Noetzel, Ida; Becker, Linda; Gräfin v. Plettenberg, Elisabeth; Kehne, Miriam (Forum Kinder- und Jugendsport)
Die Studienlage zum Thema Bewegung, Spiel und Sport im schulischen Ganztag in Deutschland zeigt sich vielseitig. Das Forschungsfeld ist neben wenigen umfassenden, überregionalen Studien durch kleinere Studien mit spezifischen inhaltlichen Schwerpunkten gekennzeichnet. Das vorliegende Scoping Review zielt darauf ab, die Erkenntnisse des Forschungsfeldes der circa vergangenen 20 Jahre zu systematisieren. Leitend ist die Forschungsfrage „Wie stellt sich der aktuelle Forschungsstand im Feld von Bewegung, Spiel und Sport im schulischen Ganztag in Deutschland dar?“ Auf Basis einer systematischen Literaturrecherche in fünf Datenbanken konnten aus 2365 Publikationen 52 in die Analyse eingeschlossen werden. Überwiegend wurden regionale Querschnittsstudien mit spezifischem Fokus durchgeführt. Die Studien befassen sich zumeist mit den Rahmenbedingungen von Bewegung, Spiel und Sport im Ganztag sowie mit den Charakteristika von Bewegung, Spiel und Sport im Ganztag. Die Analyse verdeutlicht unter anderem den Mangel an längsschnittlichen Studien sowie den Forschungsbedarf im Bereich der Qualität von Bewegung in diesem Setting.
Keywords: Review; Ganztag; Bewegung; Spiel; Sport; Forschungsstand

Homiletischer "freejazz". Des Gerechten Gebet vermag viel. Eine Partytour - Schroeter-Wittke, Harald; Scheidegger, Martin (Pastoraltheoogie)

Kritische Mathematik und die Axiomatik Hilberts - Peckhaus, Volker (Der Geist der kritischen Schule. Kantisches Denken in der Tradition von Jakob Friedrich Fries und Leonard Nelson im 20. Jahrhundert: Wirkungen und Aktualität)

Pop-Ikonen. Transformationen des Heiligen in der deutschen Pop(musik)kultur. - Jacke, Christoph; Schroeter-Wittke, Harald ((Un)verfügbar. Kulturen des Heiligen.)

Quasimodogeniti (07.04.2024) Joh 20,19-20(21-23)24-29: Vom Safe Space zum Escape Room: Der gläubige Thomas - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Seven Psalms. Paul Simons theologische Kammermusik - Schroeter-Wittke, Harald (Praktische Theologie)

Time and Space Optimized Storage-based BIST under Multiple Voltages and Variations - Jafarzadeh, Hanieh; Klemme, Florian; Amrouch, Hussam; Hellebrand, Sybille; Wunderlich, Hans-Joachim (European Test Symposium, The Hague, Netherlands, May 20-24, 2024)

Von Transzendenz zum Transhumanismus. Deutungskulturen von (Un-)Heilsgeschichte im 19. und 20. Jahrhundert

Weihnachts-Werbespots als moderne Krippenspiele

A Comparison of the Most Intense Periods (MIPs) During Competitive Matches and Training Over an 8-Week Period in a Male Elite Field Hockey Team - Büchel, Daniel; Döring, Michael; Baumeister, Jochen (Journal of Science in Sport and Exercise)
Abstract Purpose Wearables serve to quantify the on-court activity in intermittent sports such as field hockey (FH). Based on objective data, benchmarks can be determined to tailor training intensity and volume. Next to average and accumulated values, the most intense periods (MIPs) during competitive FH matches are of special interest, since these quantify the peak intensities players experience throughout the intermittent matches. The aim of this study was to retrospectively compare peak intensities between training and competition sessions in a male FH team competing in the first german division. Methods Throughout an 8-week in-season period, 372 individual activity datasets (144 datasets from competitive sessions) were recorded using the Polar Team Pro sensor (Kempele, Finland). MIPs were calculated applying a rolling window approach with predefined window length (1–5 min) and calculated for Total distance, High-Intensity-Running distance (> 16 km/h), Sprinting distance (> 20 km/h) and Acceleration load. Significant differences between training and competition MIPs were analysed through non-parametric statistical tests ( P < 0.05). Results Analyses revealed higher MIPs during competition for all considered outcomes ( P < 0.001). Effect size estimation revealed strongest effects for sprinting distance ( d = 1.89 to d = 1.22) and lowest effect sizes for acceleration load ( d = 0.92 to d = 0.49). Conclusion The present findings demonstrate that peak intensities during training do not reach those experienced during competitive sessions in a male FH team. Training routines such as manipulations of court-dimensions and team sizes might contribute to this discrepancy. Coaches should compare training and competition intensities to recalibrate training routines to optimize athletes’ preparation for competition.
Keywords: Nutrition and Dietetics; Rehabilitation; Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; Physiology

Adding Why to What? Analyses of an Everyday Explanation - Terfloth, Lutz; Schaffer, Michael; Buhl, Heike M.; Schulte, Carsten
In XAI it is important to consider that, in contrast to explanations for professional audiences, one cannot assume common expertise when explaining for laypeople. But such explanations between humans vary greatly, making it difficult to research commonalities across explanations. We used the dual nature theory, a techno-philosophical approach, to cope with these challenges. According to it, one can explain, for example, an XAI's decision by addressing its dual nature: by focusing on the Architecture (e.g., the logic of its algorithms) or the Relevance (e.g., the severity of a decision, the implications of a recommendation). We investigated 20 game explanations using the theory as an analytical framework. We elaborate how we used the theory to quickly structure and compare explanations of technological artifacts. We supplemented results from analyzing the explanation contents with results from a video recall to explore how explainers justified their explanation. We found that explainers were focusing on the physical aspects of the game first (Architecture) and only later on aspects of the Relevance. Reasoning in the video recalls indicated that EX regarded the focus on the Architecture as important for structuring the explanation initially by explaining the basic components before focusing on more complex, intangible aspects. Shifting between addressing the two sides was justified by explanation goals, emerging misunderstandings, and the knowledge needs of the explainee. We discovered several commonalities that inspire future research questions which, if further generalizable, provide first ideas for the construction of synthetic explanations.

Ambivalenzkompetenz? Rückblick auf die Tagung "Katastrophen". Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert am Vortag des russischen Angriffs auf die Ukraine - Schroeter-Wittke, Harald; Breckner, Anne (Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert)

Ambivalenzkompetenz? Rückblick auf die Tagung 'Katastrophen'. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert am Vortag des russischen Angriffs auf die Ukraine - Breckner, Anne; Schroeter-Wittke, Harald (Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert)

Angelica Dinger: Basileia bei Origenes. Historisch-semantische Analysen im Matthäuskommentar. Beiträge zur historischen Theologie 194. Mohr Siebeck, Tübingen 2020, 338 S. - Schroeter-Wittke, Harald (Paderborner Historische Mitteilungen)

Aushandlungen von Inklusion und Exklusion im Kontext der (nicht-)Verfügbarkeit mobiler Medien. Ein rekonstruktiver Blick auf die Mediatisierung berufsschulischer Möglichkeitsräume. - Dehmel, Lukas; Meister, Dorothee (Jahrbuch Medienpädagogik 20. Inklusive Medienbildung in einer mediatisierten Welt. Medienpädagogische Perspektiven auf ein interprofessionelles Forschungsfeld.)

Bibelfeste Terroristen, laichende Aale und eine frustrierte Polizeichefin. Syllas Tzoumerkas Film "Das Wunder im Meer von Sargasso" - Janus, Richard (ta katoptrizomena - Magazin für Kunst, Kultur, Theologie)

Christine Schwanecke: A Narratology of Drama: Dramatic Storytelling in Theory, History, and Culture from the Renaissance to the Twenty-First Century - Tönnies, Merle

Cognitive Training Improves Joint Stiffness Regulation and Function in ACLR Patients Compared to Healthy Controls - An, Yong Woo; Kim, Kyung-Min; DiTrani Lobacz, Andrea; Baumeister, Jochen; Higginson, Jill S.; Rosen, Jeffrey; Swanik, Charles Buz (Healthcare)
As cognitive function is critical for muscle coordination, cognitive training may also improve neuromuscular control strategy and knee function following an anterior cruciate ligament reconstruction (ACLR). The purpose of this case-control study was to examine the effects of cognitive training on joint stiffness regulation in response to negative visual stimuli and knee function following ACLR. A total of 20 ACLR patients and 20 healthy controls received four weeks of online cognitive training. Executive function, joint stiffness in response to emotionally evocative visual stimuli (neutral, fearful, knee injury related), and knee function outcomes before and after the intervention were compared. Both groups improved executive function following the intervention (p = 0.005). The ACLR group had greater mid-range stiffness in response to fearful (p = 0.024) and injury-related pictures (p = 0.017) than neutral contents before the intervention, while no post-intervention stiffness differences were observed among picture types. The ACLR group showed better single-legged hop for distance after cognitive training (p = 0.047), while the healthy group demonstrated no improvement. Cognitive training enhanced executive function, which may reduce joint stiffness dysregulation in response to emotionally arousing images and improve knee function in ACLR patients, presumably by facilitating neural processing necessary for neuromuscular control.
Keywords: Health Information Management; Health Informatics; Health Policy; Leadership and Management

Comparison of ex- and in-situ investigations of clinched single-lap shear specimens - Köhler, Daniel; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (Materials Research Proceedings)
Abstract. Force-displacement measurements and macrosections are commonly used methods to validate numerical models of clinching processes. However, these ex-situ methods often lead to springback of elastic deformations and crack-closing after unloading. In contrast, the in-situ computed tomography (CT) can provide three-dimensional images of the clinching point under loading conditions. So far, the quantity of elastic springback that causes measuring deviations between in- and ex-situ measurements is not determined. In this paper, a method is described to quantitatively compare the results of in-situ CT, ex-situ CT and CT scans of cut specimens, which are prepared for macrosectioning, among each other. The method is applied to a single-lap shear test of two clinched aluminum sheets. Here, the test is conducted to specific process steps, then the specimen is CT scanned in-situ (during loading) and ex-situ (after unloading). Subsequently, the specimens are cut for macrosectioning and CT scanned. Finally, the outer contours and the interfaces of cross section images are determined by digital image analysis and the deviations over the clinching point between ex- and in-situ methods are calculated.

Déjà vu. Sebald wiederlesen - Öhlschläger, Claudia (Nebelflecken und das Unbeobachtete. Neue Forschungsansätze zum Werk W.G. Sebalds im 20. Todesjahr.)

Die Kreuzzüge. Militärisches Mönchtum, Kirchlicher Imperialismus, Gottesfurcht und Menschenverachtung - Janus, Richard

Die Totenmaske als Medium der kleinen Form. Zur Mehrdeutigkeit von Ahnenkult und Historie im frühen 20. und 21. Jahrhundert - Öhlschläger, Claudia (Scientia Poetica)

Einfluss der Radhubkinematik auf den Reifenverschleiß - Schütte, Jan; Sextro, Walter (20. VDI-Fachtagung Reifen - Fahrwerk - Fahrbahn)

Full Breastfeeding and Allergic Diseases—Long-Term Protection or Rebound Effects? - Libuda, Lars; Filipiak-Pittroff, Birgit; Standl, Marie; Schikowski, Tamara; von Berg, Andrea; Koletzko, Sibylle; Bauer, Carl-Peter; Heinrich, Joachim; Berdel, Dietrich; Gappa, Monika (Nutrients)
A previous follow-up of the GINIplus study showed that breastfeeding could protect against early eczema. However, effects diminished in adolescence, possibly indicating a “rebound effect” in breastfed children after initial protection. We evaluated the role of early eczema until three years of age on allergies until young adulthood and assessed whether early eczema modifies the association between breastfeeding and allergies. Data from GINIplus until 20-years of age (N = 4058) were considered. Information on atopic eczema, asthma, and rhinitis was based on reported physician’s diagnoses. Adjusted Odds Ratios (aOR) were modelled by using generalized estimating equations. Early eczema was associated with eczema (aORs = 3.2–14.4), asthma (aORs = 2.2–2.7), and rhinitis (aORs = 1.2–2.7) until young adulthood. For eczema, this association decreased with age (p-for-interaction = 0.002–0.006). Longitudinal models did not show associations between breastfeeding and the respective allergies from 5 to 20 years of age. Moreover, early eczema generally did not modify the association between milk feeding and allergies except for rhinitis in participants without family history of atopy. Early eczema strongly predicts allergies until young adulthood. While preventive effects of full breastfeeding on eczema in infants with family history of atopy does not persist until young adulthood, the hypothesis of a rebound effect after initial protection cannot be confirmed.
Keywords: Food Science; Nutrition and Dietetics

Impact of COVID-19 on the private and professional lives of highly educated women working in global health in Europe—A qualitative study - Hoffmann, Christina; Schneider, Tamara; Wannous, Chadia; Nyberger, Karolina; Haavardsson, Ingeborg; Gilmore, Brynne; Quigley, Paula; Winkler, Andrea S.; Ludwig, Sabine (Frontiers in Global Women's Health)
Background The COVID-19 pandemic has led to a deepening of existing inequalities and a rollback of achievements made in gender equality. Women in Global Health (WGH) is a global movement that aims to achieve gender equality in health and increase female leadership in global health. Here, the aim was to understand how the pandemic affects the private and professional lives of women working in global health in different European countries. Suggestions for future pandemic preparedness including how gender perspectives should be integrated into pandemic preparedness and how a women's network such as WGH helped them to overcome the impact of the pandemic were explored. Methods Qualitative semi-structured interviews were conducted in September 2020 with a sample size of nine highly educated women with a mean age of 42.1 years from the different WGH European chapters. The participants were informed of the study and were formally asked for their consent. The interviews were held in English via an online videoconference platform and lasted 20–25 min each. The interviews were audio recorded and transcribed verbatim. Thematic analysis was conducted according to Mayring Qualitative Content Analysis using MAXQDA. Results The pandemic has both positive and negative effects on the professional and private lives of women. It led to an increased workload and stress as well as pressure to publish on COVID-19-related themes. Increased childcare and household responsibilities represented a double burden. The available space was limited if other family members were also working from home. Positive aspects included more time for family or partners and reduced travel. The participants report on perceived gender differences in the experience of the pandemic. International cooperation is considered to be a key factor for future pandemic preparedness. Being part of a women's network such as WGH was perceived as being very supportive in difficult situations during the pandemic. Conclusion This study provides unique insights into the experiences of women working in global health in different European countries. The COVID-19 pandemic influences their professional and private lives. Perceived gender differences are reported and suggest the need for integrating gender perspectives in pandemic preparedness. Networks for women, such as WGH, can facilitate the exchange of information in crises and provide women with professional and personal support.
Keywords: Industrial and Manufacturing Engineering; Environmental Engineering

Inklusion und Religionsunterricht. Einführung in eine heterogenitätssensible Religionspädagogik - Janus, Richard

Internationale Finanzkontrollen: Griechenland unter internationaler Kuratel im 19. und 21. Jahrhundert - Schönhärl, Korinna (Schulden machen: Praktiken der Staatsverschuldung im langen 20. Jahrhundert)
Ob als Effekt staatlicher Hilfspakete, als kontroverses Thema des EU-Haushalts oder als mögliche Ursache der rasant steigenden Inflation – in einer Welt im Krisenmodus ist das Problem der Staatsverschuldung aktuell wie selten zuvor. Wie und von wem aber werden Staatsschulden tatsächlich »gemacht«? Und wie stellt sich dies in der historischen Perspektive dar? Die Essays dieses Bandes machen das abstrakte Phänomen der öffentlichen Verschuldung und die verborgenen Prozesse hinter den Schuldenquoten zugänglich. Prägende Praktiken der Staatsverschuldung verdeutlichen die Beiträge anhand von fünf Kategorien: den beteiligten Akteuren, den konkreten Artefakten, den politischen Debatten, den globalen Relationen sowie der Zeitlichkeit der Verschuldung der öffentlichen Haushalte.
Keywords: Financial History; Public Debt; Economic History

Isolating Personal Knowledge Spillovers: Coinventor Deaths and Spatial Citation Differentials - Balsmeier, Benjamin; Fleming, Lee; Lück, Sonja (American Economic Review: Insights)
We propose a new method to estimate and isolate the localization of knowledge spillovers due to the physical presence of a person, using after-application but pre-grant deaths of differently located coinventors of the same patent. The approach estimates the differences in local citations between the deceased and still-living inventors at increasingly distant radii. Patents receive 26 percent fewer citations from within a radius of 20 miles around the deceased, relative to still-living coinventors. Differences attenuate with time and distance, are stronger when still-living coinventors live farther from the deceased, and hold for a subsample of possibly premature deaths. (JEL O31, O33, O34, R32)
Keywords: Management; Monitoring; Policy and Law; Geography; Planning and Development

Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert

Kosmische Christologie. Schöpfung und Erlösung in Kol 1,15–20, - Taschl-Erber, Andrea (Theologie und Glaube)

Lösungsstrategien für das Halbhohlstanznieten von höchstfesten und ultrahöchstfesten Stählen mit Aluminiumwerkstoffen - Uhe, Benedikt; Meschut, Gerson
Aufgrund der Leichtbauweise von Fahrzeugkarosserien werden konventionelle Stahlgüten durch ultrahöchstfeste Stahlwerkstoffe ersetzt. Die hohe Festigkeit dieser Werkstoffe stellt eine Herausforderung für das mechanische Fügen dar. Weil diese Stahlwerkstoffe zunehmend in erhöhter Dicke eingesetzt werden, wird die Leistungsfähigkeit konventioneller Halbhohlstanzniete überschritten. Im Rahmen des Forschungsvorhabens wurde ein Stanzniet erarbeitet, welcher eine Erweiterung des Einsatzbereichs des Halbhohlstanznietens auf stempelseitige Fügeteile aus höchstfesten und ultrahöchstfesten Stahlwerkstoffen bei großer Materialdicke ermöglicht. Zunächst wurden Referenzverbindungen mit handelsüblichen Stanznieten erstellt und analysiert. Durch die simulationsgestützte Ermittlung der Spannungs- und Dehnungsverhältnisse im Stanzniet wurden Ansätze für die Modifizierung der Stanzniete erarbeitet. Ebenso wurde der Einfluss der einzelnen Geometrieparameter des Stanzniets auf die Verformung des Stanzniets und die Verbindungsausbildung untersucht. Parallel dazu, wurden die mechanischen Eigenschaften potenzieller Stanznietwerkstoffe charakterisiert und eine angepasste Wärmebehandlungsstrategie erarbeitet. Durch die Modifizierung der Werkstofflegierung und der Wärmebehandlung kann eine Erhöhung der Festigkeit des Stanznietwerkstoffs um ca. 20 % gegenüber der bisher üblichen Härteklasse H6 erreicht werden. Daher kann eine Stanznietgeometrie mit einem bisher üblichen Nenndurchmesser von 5,5 mm verwendet werden. Die neuen Stanzniete wurden experimentell in einem zweistufigen Kaltumformprozess hergestellt. Abschließend wurde die erarbeitete Lösung basierend auf experimentellen Versuchen analysiert.

Mahlzeit! Essen ist mehr als Nahrungsaufnahme - Janus, Richard

Measurement, Modelling, and Appli cation of Lubricant Properties at Extreme Pressures - Wingertszahn, Patrick; Schmitt, Sebastian; Thielen, Stefan; Oehler, Manuel; Magyar, Balázs; Koch, Oliver; Hasse, Hans; Stephan, Simon (Tribologie und Schmierungstechnik)
Lubricants play a central role in many technical applications, e.g. in bearings and gears as well as in machining processes. In such applications, lubricants are exposed to extreme conditions in the contact area. In lubrication gaps, the pressure can reach values up to 5 GPa. The thermophysical properties of lubricants, and in particular the viscosity, at such extreme conditions have an important influence on the friction and wear behavior of a tribosystem. Accordingly, reliable lubricant property models are a prerequisite for accurate tribological simulations, e.g. elastohydrodynamic lubrication (EHL) simulations. Presently, the vast majority of experimental thermophysical property data are only available up to 1 GPa. Thus, reliable and robust models with strong extrapolation capabilities to higher pressure are required. In this work, viscosity measurements of squalane in a temperature range be tween 20 °C and 100 °C and pressures up to 1 GPa were carried out. Based on that data, a physical model for the viscosity was developed. The model is built by combining a molecular-based equation of state with the so-called entropy scaling approach. Finally, we demonstrate how this fluid property model can be favorably integrated in an EHL simulation by an application programming interface (API). The novel hybrid modeling approach is promising for future applications.
Keywords: Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanical Engineering; Mechanics of Materials

Molecular Adhesion of a Pilus‐derived Peptide Involved in Pseudomonas aeruginosa Biofilm Formation on non‐polar ZnO Surfaces - Prüßner, Tim; Meinderink, Dennis; Zhu, Siqi; Orive, Alejandro G.; Kielar, Charlotte; Huck, Marten; Steinrück, Hans-Georg; Keller, Adrian; Grundmeier, Guido (Chemistry – A European Journal)
Bacterial colonization and biofilm formation on abiotic surfaces are initiated by the adhesion of peptides and proteins. Understanding the adhesion of such peptides and proteins at a molecular level thus represents an important step toward controlling and suppressing biofilm formation on technological and medical materials. This study investigates the molecular adhesion of a pilus‐derived peptide that facilitates biofilm formation of Pseudomonas aeruginosa, a multidrug‐resistant opportunistic pathogen frequently encountered in healthcare settings. Single‐molecule force spectroscopy (SMFS) was performed on chemically etched ZnO surfaces to gather insights about peptide adsorption force and its kinetics. Metal‐free click chemistry for the fabrication of peptide‐terminated SMFS cantilevers was performed on amine‐terminated gold cantilevers and verified by X‐ray photoelectron spectroscopy (XPS) and polarization‐modulated infrared reflection absorption spectroscopy (PM‐IRRAS). Atomic force microscopy (AFM) and XPS analyses reveal stable topographies and surface chemistries of the substrates that are not affected by SMFS. Rupture events described by the worm‐like chain model (WLC) up to 600 pN were detected for the non‐polar ZnO(11‐20) surfaces. The dissociation barrier energy at zero force ΔG(0), the transition state distance xb and bound‐unbound dissociation rate at zero force koff(0) for the single crystalline substrate indicate that coordination and hydrogen bonds dominate the peptide/surface interaction.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Musikwelten der Wiener Moderne. Das Beispiel der künstlerischen Emanzipation der Musikerin Smaragda Eger-Berg - Ricke, Anna (It's a Man's World? Künstlerinnen in Europas Musik-Metropolen des frühen 20. Jahrhunderts)

Nächstes Jahr in Jerusalem – oder auch nicht. Perspektiven auf Deutschland und Israel in Olga Grjasnowas "Der Russe ist einer, der Birken liebt" und Mirna Funks "Winternähe" - Spener, Anna Maria (DINGS 2021. Beiträge zur Digitalen INternationalen Germanistischen Studierendentagung. Literatur des 20. und 21. Jahrhunderts)

No effects of different perturbations on the performance in a mental body-rotation task (MBRT) with egocentric perspective transformations and object-based transformations - Budde, Kirsten; Weigelt, Matthias (Human Movement Science)
The present study investigates participants' performance in two different mental body-rotation tasks (MBRTs) under conditions in which dynamic stability is challenged in two different balancing conditions: active balance control (Experiment 1), where participants actively maneuver, and re-active balance control (Experiment 2), where participants react to an external perturbation. The two MBRTs induced either an object-based spatial transformation (based on a same-different judgment) or an egocentric transformation (based on a left-right judgment). In Experiment 1, 48 participants were tested while standing on an even ground (low balancing requirements) or on a balance board (high balancing requirements). In Experiment 2, 32 participants performed while either standing still on a vibration plate or with the vibration plate moving in a low (20 Hz) or high (180 Hz) frequency. In both experiments, the results for response time and response error revealed effects of rotation angle and type of task. An effect of balancing condition was only observed for response error in Experiment 1. More precisely, response times and response errors increased for higher rotation angles. Also, performance was better for egocentric than for object-based spatial transformations. However, the different challenges to dynamic stability in Experiments 1 and 2 did not influence performance in the two MBRTs (except for response errors in Experiment 1) nor in a control condition (Experiment 1) without mental rotation.
Keywords: Mental rotation; Balance control; Perturbation; Embodiment

Pre-equilibrium photons from the early stages of heavy-ion collisions - Oscar Garcia-Montero, Oscar Garcia-Montero; Mazeliauskas, Aleksas; Plaschke, Philip; Schlichting, Sören (arXiv:2308.09747)
We use QCD kinetic theory to compute photon production in the chemically equilibrating Quark-Gluon Plasma created in the early stages of high-energy heavy-ion collisions. We do a detailed comparison of pre-equilibrium photon rates to the thermal photon production. We show that the photon spectrum radiated from a hydrodynamic attractor evolution satisfies a simple scaling form in terms of the specific shear viscosity $η/s$ and entropy density $dS/dζ \sim {\scriptstyle \left(Tτ^{1/3}\right)^{3/2}}_∞$. We confirm the analytical predictions with numerical kinetic theory simulations. We use the extracted scaling function to compute the pre-equilibrium photon contribution in $\sqrt{s_{NN}}=2.76\,\text{TeV}$ 0-20% PbPb collisions. We demonstrate that our matching procedure allows for a smooth switching from pre-equilibrium kinetic to thermal hydrodynamic photon production. Finally, our publicly available implementation can be straightforwardly added to existing heavy ion models.

Protein intake and body weight, fat mass and waist circumference: an umbrella review of systematic reviews for the evidence-based guideline on protein intake of the German Nutrition Society - Ellinger, Sabine; Amini, Anna M.; Haardt, Julia; Lehmann, Andreas; Schmidt, Annemarie; Bischoff-Ferrari, Heike A.; Buyken, Anette; Kroke, Anja; Kühn, Tilman; Louis, Sandrine; Lorkowski, Stefan; Nimptsch, Katharina; et al. (European Journal of Nutrition)
Abstract Purpose This umbrella review aimed to assess whether dietary protein intake with regard to quantitative (higher vs. lower dietary protein intake) and qualitative considerations (total, plant-based or animal-based protein intake) affects body weight (BW), fat mass (FM) and waist circumference (WC). Methods A systematic literature search was conducted in PubMed, Embase and Cochrane Database of Systematic Reviews for systematic reviews (SRs) with and without meta-analyses of prospective studies published between 04 October 2007 and 04 January 2022. Methodological quality and outcome-specific certainty of evidence of the retrieved SRs were assessed by using AMSTAR 2 and NutriGrade, respectively, in order to rate the overall certainty of evidence using predefined criteria. Results Thirty-three SRs were included in this umbrella review; 29 were based on randomised controlled trials, a few included cohort studies. In studies without energy restriction, a high-protein diet did not modulate BW, FM and WC in adults in general (all “possible” evidence); for older adults, overall certainty of evidence was “insufficient” for all parameters. Under hypoenergetic diets, a high-protein diet mostly decreased BW and FM, but evidence was “insufficient” due to low methodological quality. Evidence regarding an influence of the protein type on BW, FM and WC was “insufficient”. Conclusion “Possible” evidence exists that the amount of protein does not affect BW, FM and WC in adults under isoenergetic conditions. Its impact on the reduction in BW and FM under hypoenergetic conditions remains unclear; evidence for an influence of protein type on BW, FM and WC is “insufficient”.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Reformation mit Dorothee Sölle feiern. 31. Oktober 2023

Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert

Responses to heat waves: what can Twitter data tell us? - Zander, Kerstin K.; Rieskamp, Jonas; Mirbabaie, Milad; Alazab, Mamoun; Nguyen, Duy (Natural Hazards)
Abstract Increasing average temperatures and heat waves are having devasting impacts on human health and well-being but studies of heat impacts and how people adapt are rare and often confined to specific locations. In this study, we explore how analysis of conversations on social media can be used to understand how people feel about heat waves and how they respond. We collected global Twitter data over four months (from January to April 2022) using predefined hashtags about heat waves. Topic modelling identified five topics. The largest (one-third of all tweets) was related to sports events. The remaining two-thirds could be allocated to four topics connected to communication about climate-related heat or heat waves. Two of these were on the impacts of heat and heat waves (health impacts 20%; social impacts 16%), one was on extreme weather and climate change attribution (17%) and the last one was on perceptions and warning (13%). The number of tweets in each week corresponded well with major heat wave occurrences in Argentina, Australia, the USA and South Asia (India and Pakistan), indicating that people posting tweets were aware of the threat from heat and its impacts on the society. Among the words frequently used within the topic ‘Social impacts’ were ‘air-conditioning’ and ‘electricity’, suggesting links between coping strategies and financial pressure. Apart from analysing the content of tweets, new insights were also obtained from analysing how people engaged with Twitter tweets about heat or heat waves. We found that tweets posted early, and which were then shared by other influential Twitter users, were among the most popular. Finally, we found that the most popular tweets belonged to individual scientists or respected news outlets, with no evidence that misinformation about climate change-related heat is widespread.
Keywords: Earth and Planetary Sciences (miscellaneous); Atmospheric Science; Water Science and Technology

Robot leadership–Investigating human perceptions and reactions towards social robots showing leadership behaviors - Cichor, Jakub Edward; Hubner-Benz, Sylvia; Benz, Tobias; Emmerling, Franziska; Peus, Claudia (PLOS ONE)
Human-robot interaction research has shown that social robots can interact with humans in complex social situations and display leadership-related behaviors. Therefore, social robots could be able to take on leadership roles. The aim of our study was to investigate human followers’ perceptions and reactions towards robot leadership behavior, and differences based on the robot’s displayed leadership style. We implemented a robot to show either a transformational or a transactional leadership style in its speech and its movements. We presented the robot to university and executive MBA students (N = 29) and subsequently conducted semi-structured interviews and group discussions. The results of explorative coding indicated that participants differed in their perceptions and reactions based on the robot’s leadership style and based on their assumptions about robots in general. We observed that participants quickly imagined either a utopia or worried about a dystopia, depending on the robot’s leadership style and their assumptions, and that a subsequent reflection led to more nuanced views. We discuss the implications and recommendations for human-robot interaction and leadership research.
Keywords: Multidisciplinary

Tagungsbericht: 10/20 Jahre UNESCO-Konvention zum Erhalt des Immateriellen Kulturerbes – Auftaktveranstaltung zum Doppeljubiläum - Leineweber, Jonas

Thorsten Knauth/Rainer Möller/Annebelle Pithan (Hg.), Inklusive Religionspädagogik der Vielfalt. Konzeptionelle Grundlagen und didaktische Konkretionen. Münster/New York 2020 - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

Towards Interpretability in Audio and Visual Affective Machine Learning: A Review - Johnson, David; Hakobyan, Olya; Drimalla, Hanna
Machine learning is frequently used in affective computing, but presents challenges due the opacity of state-of-the-art machine learning methods. Because of the impact affective machine learning systems may have on an individual's life, it is important that models be made transparent to detect and mitigate biased decision making. In this regard, affective machine learning could benefit from the recent advancements in explainable artificial intelligence (XAI) research. We perform a structured literature review to examine the use of interpretability in the context of affective machine learning. We focus on studies using audio, visual, or audiovisual data for model training and identified 29 research articles. Our findings show an emergence of the use of interpretability methods in the last five years. However, their use is currently limited regarding the range of methods used, the depth of evaluations, and the consideration of use-cases. We outline the main gaps in the research and provide recommendations for researchers that aim to implement interpretable methods for affective machine learning.

Training matters: Heading incidence and characteristics in children's and youth football (soccer) players - Reeschke, Rebecca; Haase, Franziska Katharina; Dautzenberg, Lena; Krutsch, Werner; Reinsberger, Claus (Scandinavian Journal of Medicine & Science in Sports)
Abstract Objective Concerns about short‐ and long‐term consequences of repetitive heading contributed to heading restrictions in youth football in some countries. This prospective longitudinal cohort study aims to describe heading exposure in children's and youth football over two seasons using standardized video analysis. Methods All matches and training sessions of a male Under‐11 ( n = 29), Under‐15 ( n = 28), Under‐19 ( n = 38), and female Under‐17 ( n = 39) team were videotaped during the seasons 2019–2020 and 2020–2021. Heading frequencies and characteristics were analyzed. Individual heading exposure is presented as average incidence rates (IR) per 1000 match/training hours. Results In 275 matches and 673 training sessions, 22 921 headers were observed. Heading IR per player in matches was 1256 (Under‐11 m), 1608 (Under‐15 m), 1050 (Under‐17 f), and 1966 (Under‐19 m). In training sessions, IR per player was 739 (Under‐11 m), 2206 (Under‐15 m), 1661 (Under‐17 f), and 1419 (Under‐19 m). Five Under‐15 males headed the ball five to eight times per training on average. Most headers were performed without heading duels. Flight distance was predominantly 5–20 m (54%) in matches and <5 m (65%) in training. While head impact location most frequently was at frontal areas, one‐third of all headers in Under‐11 in matches hit temporal, parietal, and occipital parts of the head. Conclusion Heading incidence was low in the youngest age group, whereas (predominantly five) Under‐15 males showed very high heading exposures in training. In assessment and regulation of heading burden, training sessions and individual heading behavior should specifically be addressed. Recommendations for heading the ball in practice should account for individual and age‐related differences.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Wir haben Gottes Spuren festgestellt (EG.E 20) - Schroeter-Wittke, Harald (Ich lobe meinen Gott, der aus der Tiefe mich holt. Hymnologische Kommentare zu den Liedern im Ergänzungsheft zum Evangelischen Gesangbuch. Jan Janssen zum 60. Geburtstag. HEG 3/Ergänzungsheft, Göttingen 2023)

Zwischen lebensunwertem und selbstbestimmtem Leben. Impulse des 20. Jahrhunderts für eine ableismuskritische Religionspädagogik - Neumann, Anna (Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert)